Organophosphate pesticides and progression of chronic kidney disease among children: A prospective cohort study. (October 2021) - Jacobson, Melanie H.; Wu, Yinxiang; Liu, Mengling; Kannan, Kurunthachalam; Li, Adela Jing; Robinson, Morgan; Warady, Bradley A.; Furth, Susan; Trachtman, Howard; Trasande, Leonardo
Highlights: Longitudinally measured organophosphate pesticide metabolites and renal function. Serially measured dialkyl phosphate metabolites were associated with tubular injury. The association was strongest for diethyl metabolites. Dialkyl phosphate metabolites were associated with higher oxidant stress biomarkers. Organophosphate pesticides are potentially modifiable risk factors for renal damage. Abstract: Background: Growing evidence suggests that exposure to environmental chemicals, such as pesticides, impacts renal function and chronic kidney disease (CKD). However, it is not clear if pesticides may affect CKD progression and no studies exist in children. Objectives: The objective of this study was to examine associations between serially measured urinary OP pesticide metabolites and clinical and laboratory measures of kidney function over time among children with CKD. Methods: This study used data on 618 participants enrolled in the CKD in Children study (CKiD), a cohort study of pediatric CKD patients from the US and Canada. Children were followed over an average of 3.0 years (standard deviation (SD) = 1.6) between 2005 and 2015. In serially collected urine samples over time, six nonspecific dialkyl phosphate (DAP) metabolites of OP pesticides were measured. Biomarkers of tubular injury (kidney injury molecule-1 (KIM-1) and neutrophil gelatinase-associated lipocalin (NGAL)) and oxidant stress (8-hydroxy-2′-deoxyguanosine (8-OHdG) and F2 -isoprostane) were determined in the same specimens. Estimated glomerular filtration rate (eGFR), proteinuria, and blood pressure were assessed annually. Results: DAPs were associated with increased KIM-1 and 8-OHdG throughout follow-up. A standard deviation increase in ∑diethyl metabolites was associated with increases of 11.9% (95% Confidence Interval (CI): 4.8%, 19.4%) and 13.2% (95% CI: 9.3%, 17.2%) in KIM-1 and 8-OHdG over time, respectively. DAPs were associated with lower eGFR at baseline and higher eGFR over subsequent years. Conclusions: These findings provide preliminary evidence suggesting that urinary DAP metabolites are associated with subclinical kidney injury among children with CKD, which may signal the potential for clinical events to manifest in the future. The results from this study are significant from both a clinical and public health perspective, given that OP pesticide exposure is a modifiable risk factor.